The effect of oxygen concentration on arterial blood gas values during maintenance of anesthesia in patients undergoing lower extremity surgery (prospective, randomized, clinical study) - Bayindir, Serpil; Bestas, Azize (Bayrakol Medical Publisher, 2025)
Aim: Due to hypoventilation, an increase in pulmonary shunts, and a decrease in functional residual capacity during general anesthesia, a higher concentration of O2 (20.8%) than the atmospheric rate is required. In the intraoperative period, anesthesia maintenance can be achieved by using different ratios of O2, dry air, and nitrogen protoxide (N2O). This proportional effect can be determined by blood gas parameters. This study aimed to investigate the effect of intraoperative oxygen ratios on arterial blood gas values under general anesthesia in lower extremity surgery. Material and Methods: Forty patients aged 20-65 years scheduled for ASA II lower extremity surgery were randomly divided into two groups. Group 50 was maintained with 50% O2 + 50% dry air, while Group 30 was maintained with 30% O2 + 70% N2 O and desflurane. Blood gas analysis was performed 13 times at designated times. The amounts of antiemetic and analgesic consumed postoperatively were determined. Results: In the intergroup comparison, PaO2 was higher in Group 50 intraoperatively and in the first 6 hours postoperatively, whereas the relatively higher SaO2 continued until the 1st hour postoperatively (p<0.001). Group 50 PaCO2 values were higher than Group 30 (p<0.05) at the 1st hour of the operation. Intraoperative pH values were higher in Group 30 (p<0.001). No difference was detected in terms of bicarbonate, base deficit, and PaCO2. Discussion: A comparison of 30% O2 + 70% N2O with 50% O2 + 50% air delivery for maintenance of anesthesia showed better arterial oxygenation during the intraoperative period and the first six hours postoperatively. Postoperative pain intensity, incidence of nausea and vomiting, and patient comfort were not significantly altered.
Keywords: General Anesthesia; Oxygen Concentration; Arterial Blood Gases